δD e δ18O em águas meteóricas: generalidades e método para o seu monitoramento como uma perspectiva para o estudo hidrológico no Ceará - Carlson, Lucas de Nelson Moreira (2022)
The natural isotopes 18O e 2H, being part of the water molecule, are excellent tracers of the hydrologic cycle. With natural concentrations in the order of per thousand (‰), its measurements are expressed in relation to the standard average concentration as the ocean’s, the greatest water reservoir in the planet. Processes of phase change, such as evaporation and condensation, which occur in the form of cloud precipitation, naturally characterize water. While they are strongly dependent on temperature, for its effect, the rains of the arid and semiarid climates shows different concentrations of these isotopes. The evaporation of water changes these isotopes; on the superfcial reservoirs such as lagoons and dams, it is possible to determine the losses by evaporation. Craig (1961a) analyzed over 400 samples of different waters of different origins and identifed a linear relation among these isotopes which is δ2H = 8.δ18O + 10‰. Samples which have undergone evaporation process maintained a linear relation with inclination below 8. Due to temperature effect, rains from different places presented data in different straight lines. By building a low-cost rainwater collector and making use of CRDS (Cavity Ring Down Spectroscopy) technique, a perspective for monitoring the isotopic content of meteoric waters is Ceará is shown, constituting another source of information for monitoring climatic and hydrological issues in the state.